2014
DOI: 10.1371/journal.pone.0098257
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hepatitis B Virus Pre-S Deletions with the Development of Hepatocellular Carcinoma in Qidong, China

Abstract: Background/AimTo investigate the roles of mutations in pre-S and S regions of hepatitis B virus (HBV) on the progression of hepatocellular carcinoma (HCC) in Qidong, China.MethodsWe conducted an age matched case-control study within a cohort of 2387 male HBV carriers who were recruited from August, 1996. The HBV DNA sequence in pre-S/S regions was successfully determined in 96 HCC cases and 97 control subjects. In addition, a consecutive series of samples from 11 HCC cases were employed to evaluate the pre-S d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…During the course of chronic HBV infection, a wide variety of liver diseases are observed, ranging from an asymptomatic carrier state to liver cirrhosis and HCC [16]. In our previous studies conducted in Qidong, pre- S deletion and specific mutations in BCP were confirmed to be associated with a high risk of HCC occurrence [17,18]. However, the risk of mutations in other regions of the full HBV genome was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the course of chronic HBV infection, a wide variety of liver diseases are observed, ranging from an asymptomatic carrier state to liver cirrhosis and HCC [16]. In our previous studies conducted in Qidong, pre- S deletion and specific mutations in BCP were confirmed to be associated with a high risk of HCC occurrence [17,18]. However, the risk of mutations in other regions of the full HBV genome was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the carcinogenic risk of pre- S deletion and pre- S 2 start codon mutation in pre- S gene, C1653T, and A1762T/G1764A mutations in X gene has been extensively investigated in this cohort [17,18]. Compared to those studies focusing on mutations in pre- S and X genes, only a few studies have investigated the effect of mutations in the C gene during natural HBV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have revealed that pre-S deletions, pre-S2 start codon mutations, and the T53C mutation in the pre-S2 region are related to the development of HCC [60] .…”
Section: Mutationsmentioning
confidence: 99%